2014
DOI: 10.1111/bjh.12920
|View full text |Cite
|
Sign up to set email alerts
|

PI3K‐dependent multiple myeloma cell survival is mediated by the PIK3CA isoform

Abstract: SummaryConstitutive phosphatidylinositide 3-kinase (PI3K) signalling has been implicated in multiple myeloma (MM) pathophysiology and is regarded as an actionable target for pharmacological intervention. Isoform-specific PI3K inhibition may offer the most focused treatment approach and could result in greater clinical efficacy and reduced side effects. We therefore performed isoform-specific knockdown of PIK3CA, PIK3CB, PIK3CD, and PIK3CG to analyse their individual contributions to MM cell survival and downst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 57 publications
3
24
1
Order By: Relevance
“…The discrepant cytotoxicity of copanlisib and GDC‐0941 for CLL cells despite a similar ratio of biochemical p110‐δ and p110‐α inhibition can be explained by the higher absolute potency of copanlisib for inhibiting these isoforms. In agreement with comparisons of inhibitor cytotoxicity for CLL and MCL cells with isoform selectivity profiles, RNA interference revealed that the survival of myeloma cell lines strongly depended on p110‐alpha . In contrast, co‐culture‐induced Akt phosphorylation of myeloma cells was reduced much more strongly by knock‐down of p110‐ δ than of p110‐α .…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The discrepant cytotoxicity of copanlisib and GDC‐0941 for CLL cells despite a similar ratio of biochemical p110‐δ and p110‐α inhibition can be explained by the higher absolute potency of copanlisib for inhibiting these isoforms. In agreement with comparisons of inhibitor cytotoxicity for CLL and MCL cells with isoform selectivity profiles, RNA interference revealed that the survival of myeloma cell lines strongly depended on p110‐alpha . In contrast, co‐culture‐induced Akt phosphorylation of myeloma cells was reduced much more strongly by knock‐down of p110‐ δ than of p110‐α .…”
Section: Discussionsupporting
confidence: 65%
“…In agreement with comparisons of inhibitor cytotoxicity for CLL and MCL cells with isoform selectivity profiles, RNA interference revealed that the survival of myeloma cell lines strongly depended on p110alpha. 42 In contrast, co-culture-induced Akt phosphorylation of myeloma cells was reduced much more strongly by knockdown of p110-d than of p110-a. 43 Taken together we show that the dual p110-a and p110-d-selective inhibitor copanlisib leads to remarkable, potentially clinically useful inhibition of the survival of CLL cells, which by far surpasses that by idelalisib and duvelisib, as well as by other pan-class IA inhibitors.…”
Section: Discussionmentioning
confidence: 96%
“…Studies have demonstrated that tumors with loss of the tumor suppressor PTEN , a PIP 3 phosphatase, display increased sensitivity to PI3Kβ and AKT inhibitors [1315]. In contrast, cell lines with PIK3CA mutations generally do not respond to PI3Kβ inhibitors but encouraging results have been observed with PI3Kα and AKT inhibitors [16, 17]. …”
Section: Introductionmentioning
confidence: 99%
“…Mutations in BRAF were found to improve the response to broad acting drugs, though the clinical impact of the V600E mutation is not clear yet [39, 40]. In addition, oncogenic activation of the PI3K/AKT pathway can only partially be explained by previous investigations [11, 41, 42] and thus might also be explained by the occurrence of mutations in upstream molecules such as RTKs or other growth factors.…”
Section: Discussionmentioning
confidence: 99%